An Approach to Describe Gentelligent Components in their Life Cycle. (2016) - Lachmayer, Roland; Mozgova, Iryna; Scheidel, Wieben
Abstract: Information about products and their life cycle are often required for the product development and manufacturing process. So the application of life cycle data of smart products offers new opportunities to pass information to a new product generation. In the Collaborate Research Center (CRC) 653 smart products, so called "Gentelligent Components", which collect information about themselves and from their life cycle and store it inherently, are developed. For structuring and standardization of the life cycle information a classification system is used. A classification system for gentelligent components has to consider aspects from the development, manufacturing and usage phases as well as the environment and also the remaining life cycle phase. Therefore different classification systems are compared to their suitability for gentelligent components. Based on the most suitable existing system an approach to describe gentelligent components in their life cycle is developed. The information from development and manufacturing as well as from the usage phase of components life cycle are considered. The resulted classification system is exemplified by a wheel carrier, one of the demonstrator of the CRC 653. The applied classification system shows how gentelligent components and their information can be structured and standardized.